Early-onset phenotype in a patient with an intermediate allele and a large SCA1 expansion: a case report - Guillaume Baille; Nicolas Geoffre; Anna Wissocq; Pauline Planté-Bordeneuve; Eugénie Mutez; Vincent Huin (BMC Neurology, 2024)
Abstract Background Spinocerebellar ataxia type 1, is a rare neurodegenerative disorder with autosomal dominant inheritance belonging to the polyglutamine diseases. The diagnosis of this disease requires genetic testing that may also include the search for CAT interruption of the CAG repeat tract. Case presentation One 23-years-old patient suffers from a severe ataxia, with early-onset and rapid progression of the disease. His father might have been affected, but no molecular confirmation has been performed. The genetic results were negative for the Friedreich’s ataxia, spinocerebellar ataxia type 2, 3, 6, 7 and 17. The numbers of CAG repeats in the ATXN1 gene was assessed by fluorescent PCR, tripled-primed PCR and enzymatic digestion for the search of sequence interruption in the CAG repeats. The patient carried one pathogenic allele of 61 CAG and one intermediate allele of 37 CAG in the ATXN1 gene. Both alleles were uninterrupted. Conclusions We report a rare case of spinocerebellar ataxia type 1 with an intermediate allele and a large SCA1 expansion. The determination of the absence of CAT interruption brought crucial information concerning this molecular diagnosis, the prediction of the disease and had practical consequences for genetic counseling.